Females sustain more ankle injuries than males in youth football - Sokka, T.; Hilska, M.; Vasankari, T.; Leppänen, M.; Kannus, P.; Parkkari, J.; Haapasalo, H.; Forsman, H.; Raitanen, J.; Pasanen, K. (International Journal of Sports Medicine, 2020)
This prospective study evaluated the incidence and pattern of acute injuries in youth (9- to 14-year- old) football players. Ten football clubs [n=730 players (567 males, 163 females)] participated in the 20-week follow-up study (January-June 2015). Data was collected by sending a standardized weekly SMS to players` parents/guardians with follow-up interviews for injured players. During the study period, 278 players (38%) sustained 410 acute injuries. The overall injury incidence for males and females was 6.47 (95% CI, 5.84-7.09) injuries per 1000 h of football exposure. Most injuries (40%) caused minimal absence from sports. Eighty-four percent of the injuries affected the lower extremities, with the ankle (30%), knee (17%), and thigh (16%) being the most commonly injured body sites. Females had significantly higher ankle injury rate (IRR) 1.85 (95% CI, 1.18-2.91, p=0.007) and non-contact ankle injury rate IRR 2.78 (95% CI, 1.91-4.02, p<0.001) than males. In conclusion, our results showed that the acute injury incidence among youth football is moderately high, and females are at higher risk for ankle injuries. Injury prevention programs aimed at preventing ankle injuries should be considered in the future.